Primary Cutaneous Anaplastic Large Cell Lymphoma of the Oral Cavity Successfully Treated with Brentuximab Vedotin - Federico Meconi; Roberto Secchi; Raffaele Palmieri; Sara Vaccarini; Vito Mario Rapisarda; Laura Giannì; Fabiana Esposito; Ida Provenzano; Daniela Nasso; Livio Pupo; Maria Cantonetti (Case Reports in Hematology)
Primary cutaneous anaplastic large cell lymphoma is a CD-30 positive lymphoproliferative disorder with good prognosis, usually treated with radiation therapy and surgery. Head, neck, and extremities are the most frequently involved sites. In this paper, we describe an unusual case of oral localization, recurring after skin-involving radiotherapy, successfully treated with sixteen cycles of brentuximab vedotin. This could be a more effective approach with a less detrimental toll for treating these rare disorders.